Challenges and Opportunities in Physical Education in the Digital Age: Impact on Teaching Methods - Alimin Hamzah (Journal Physical Health Recreation (JPHR), 2025)
The digital transformation has significantly reshaped the landscape of education, including the field of physical education. This study aims to analyze the challenges and opportunities of digital technology integration into teaching methods in sports education through a systematic literature review (SLR). Data were collected from 20 national and international journal articles published between 2020 and 2025. A thematic content analysis was applied focusing on three main aspects: (1) the transformation of physical education in the digital era, (2) challenges in implementing digitalization, and (3) opportunities and their impact on teaching methods. The findings indicate that digitalization presents substantial opportunities for pedagogical innovation through the application of artificial intelligence (AI), the Internet of Things (IoT), flipped classroom, and hybrid learning models, all of which enhance learning effectiveness and student engagement. However, several challenges persist, including low digital literacy among teachers, infrastructural limitations, and difficulties in assessing physical performance online. Consequently, digital transformation in sports education requires a shift in the teacher’s role—from a conventional instructor to a digital facilitator capable of adapting to technological change. This study emphasizes the need for policy support, professional development programs, and the integration of technology-based curricula to ensure the sustainability of digital transformation in physical education.